Sievietes loma Latvijas baptistu draudžu darbībā 20.gs. 60.-80.gados - Raudiņa, Ingūna (Latvijas Universitāte, 2024)
Maģistra darba tēma ir “Sievietes loma Latvijas baptistu draudžu darbībā 20.gs. 60.-80.gados”. Maģistra darbā tiek apskatīts baptistu teoloģiskais skatījums uz sievietes lomu draudzē. Padomju okupācijas gadi baptistu draudzēm nesa savus īpašus izaicinājumus, un pētījuma periodā draudzes darbība tika dažādi ierobežota. Draudzes nereti darbojās starp atļauto un neatļauto. Darbā tiek apskatīta sieviešu iesaiste baptistu draudžu darbībā. Sievietes ļoti plaši un aktīvi iesaistijās baptistu draudžu darbā. Īpaši liels sieviešu devums redzams muzikālajā darbā, svētdienskolu darbā, māsu un diakonijas kalpošanā un nelegālās literatūras pavairošanā. Sievietes lomu draudzē noteica baptistu tradīcija un draudžu autonomija. Sieviešu unikālajam un īpašajam devumam baptistu draudžu darbā līdz šim ir veltīta vien pastarpināta uzmanība.

The topic of the master's thesis is "The Role of Women in the Activity of Latvian Baptist Churches in the 20th Century 60s-80s". The master's thesis examines the theological view of the Baptists on the role of the women in the church. The years of Soviet occupation brought their own special challenges to Baptist churches, and the church's activities were restricted in various ways during the research period. Congregations often operated between the permitted and the unauthorized. The work examines the involvement of women in the activities of Baptist churches. Women were very widely and actively involved in the work of Baptist churches. A particularly large contribution of women can be seen in musical work, Sunday School work, womens ministries and deaconry service, and the production of illegal literature. The role of women in the church was determined by the Baptist tradition and the autonomy of the churches. The unique and special contribution of women to the work of Baptist churches has thus far received only passing attention.
The Role of Women in the Activity of Latvian Baptist Churches in the 20th Century 60s-80s
Keywords: Filozofija, ētika un reliģija; baptisti; Latvija; Padomju laiki; sieviete